2018
DOI: 10.1177/0032321718764800
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electoral Context on the Electoral Effectiveness of District-Level Campaigning: Popularity Equilibrium and the Case of the 2015 British General Election

Abstract: Campaigning at the district level can deliver electoral payoffs in a range of countries despite variations in electoral systems. However, effects may not be consistent. Campaigns do not occur in a vacuum, and contextual factors, exogenous to the campaign activity itself, may have a significant effect on the level of their electoral impact. The 2015 General Election in Britain is a particularly interesting case as there was a key contextual factor which could impact significantly on the effectiveness of the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The chances of dissatisfaction in more competitive seats is likely to be higher, both because the contest is likely to be harder fought and because the outcome is uncertain. Certainly, there is clear evidence that the marginality or closeness of an electoral seat increases campaign activity (Fisher et al, 2019) and the amounts spent by candidates (Johnston & Pattie, 2014). And, as Howell and Justwan (2013: 337) suggest, elections that are non-competitive (that is, they are not marginal and the outcome is clear in advance) are likely to disconnect winners and losers from results, whereas the anxiety produced in a close contest will be more likely to impact upon levels of satisfaction.…”
Section: H5 Evaluations Of Electoral Integrity Will Be More Negativementioning
confidence: 99%
See 1 more Smart Citation
“…The chances of dissatisfaction in more competitive seats is likely to be higher, both because the contest is likely to be harder fought and because the outcome is uncertain. Certainly, there is clear evidence that the marginality or closeness of an electoral seat increases campaign activity (Fisher et al, 2019) and the amounts spent by candidates (Johnston & Pattie, 2014). And, as Howell and Justwan (2013: 337) suggest, elections that are non-competitive (that is, they are not marginal and the outcome is clear in advance) are likely to disconnect winners and losers from results, whereas the anxiety produced in a close contest will be more likely to impact upon levels of satisfaction.…”
Section: H5 Evaluations Of Electoral Integrity Will Be More Negativementioning
confidence: 99%
“…The chances of dissatisfaction in more competitive seats is likely to be higher, both because the contest is likely to be harder fought and because the outcome is uncertain. Certainly, there is clear evidence that the marginality or closeness of an electoral seat increases campaign activity (Fisher et al, 2019) and the amounts spent by candidates (Johnston and Pattie, 2014). And, as Howell and Justwan (2013: 337) suggest, elections that are non-competitive (i.e.…”
Section: Predictors Of Evaluations – Theorymentioning
confidence: 99%
“…Using the same logic as macro popularity equilibrium, we would expect that local campaigns might be most effective where parties are neither very strong nor very weak. Fisher et al (2018) demonstrated that district-level campaign effectiveness varied according to the level of popularity in the constituency using data from a single election. To establish whether the popularity equilibrium model applies more generally at the district level, we need to establish the relationship between district-level popularity and performance across a number of elections.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Yet, the success of campaign activity is not solely in the hands of parties or candidates. There is emerging evidence in the literature that both national and district-level conditions affect the degree to which campaign efforts are productive (Fisher et al, 2011(Fisher et al, , 2018Fisher et al, 2016;Hillygus, 2005). However, until now, there has been no systematic theory or analysis of the conditions under which local campaigns are more or less effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation